Physical activity pattern of patients with interstitial lung disease compared to patients with COPD: A propensity-matched study - Breuls, Sofie; Pereira de Araujo, Cintia; Blondeel, Astrid; Yserbyt, Jonas; Janssens, Wim; Wuyts, Wim; Troosters, Thierry; Demeyer, Heleen (PLOS ONE, 2022)
Introduction Physical activity (PA) is reduced in patients with interstitial lung disease (ILD) and chronic obstructive pulmonary disease (COPD). Evidence about the PA pattern of patients with ILD is scarce. If PA of patients with ILD would be comparable to COPD, it is tempting to speculate that existing interventions focusing on enhancing PA could be as effective in ILD as already shown in COPD. Therefore, we aimed to compare PA and the correlates with PA in matched patients with ILD, COPD, and healthy subjects. Materials and methods Patients with ILD (n = 45), COPD (n = 45) and healthy subjects (n = 30) were propensity matched. PA level, pattern, and PA correlations with lung function and physical performance (6-minute walking distance and quadriceps force) were compared between groups. Results Daily number of steps was similar in both patient groups (mean±SE: 5631±459 for ILD, 5544±547 for COPD, p = 0.900), but significantly lower compared to healthy subjects (10031±536, p<0.001 for both). Mean intensity of PA tended to be lower in the ILD group (mean±SE metabolic equivalents of task per day: 1.41±0.04) compared to COPD (1.52±0.05, p = 0.074) and healthy individuals (1.67±0.04, p<0.001). The pattern of PA over one day was found to be similar between the three groups. Lastly, the correlation between PA and 6-minute walking distance was significantly weaker in patients with ILD compared to patients with COPD (respectively r = 0.348 and r = 0.739; p<0.05 for both). Conclusions For a given functional reserve, patients with ILD perform an equal amount of steps but perform PA at lower intensity compared to patients with COPD. Both groups are less active compared to healthy control subjects. Functional exercise capacity was shown to be only moderately related to PA. This can potentially influence the effectiveness of PA interventions that can be expected.